1998
DOI: 10.1053/euhj.1998.1084
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and heart rate in healthy volunteers. Is the female autonomic nervous system cardioprotective?

Abstract: Cardiac autonomic modulation as determined by heart rate variability, is significantly lower in healthy women compared to healthy men. We hypothesize that this apparently paradoxical finding may be explained by lower sympathetic activity (low frequency power) in women. This may provide protection against arrhythmias and against the development of coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
174
6
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(228 citation statements)
references
References 36 publications
41
174
6
7
Order By: Relevance
“…Indeed, although no significant statistical differences between HP complexity in men and women were detected in any age group, likely as a result of the low statistical power of the study for this specific endpoint, we observed that NCIHP was systematically larger in women than in men in any age group except 61-70, thus suggesting that after menopause complexity of the HP series in women dramatically dropped. This result confirmed the progressive decrease of gender differences with age reported in [13,19,23,38,41].…”
Section: Complexity Of the Hp Variability At Rest: Aging And Gender Esupporting
confidence: 88%
“…Indeed, although no significant statistical differences between HP complexity in men and women were detected in any age group, likely as a result of the low statistical power of the study for this specific endpoint, we observed that NCIHP was systematically larger in women than in men in any age group except 61-70, thus suggesting that after menopause complexity of the HP series in women dramatically dropped. This result confirmed the progressive decrease of gender differences with age reported in [13,19,23,38,41].…”
Section: Complexity Of the Hp Variability At Rest: Aging And Gender Esupporting
confidence: 88%
“…Healthy subjects over 40 years old showed a smaller decrease in HF as well as a decreasing Valsalva ratio. 34 Saito et al 3 reported the prevalence of IBS as 13.5% in under 45 seconds and 9.4% in over 45 seconds. We speculate that the decline in IBS symptoms as people age may be influenced by the reduced activity of the ANS.…”
Section: Discussionmentioning
confidence: 99%
“…The data are less consistent on the impact of sex and race. Some studies have reported that women have greater levels of HF power Ryan et al, 1994) while others report no sex difference (Evans et al, 2001;Laitinen et al, 1998;Pikkujamsa et al, 2001;Ramaekers et al, 1998). Fewer studies still report on the impact of race on RRV.…”
Section: Introductionmentioning
confidence: 99%